The fight for legitimacy : democracy vs. terrorism - Jebb, Cindy R., 1960- (Westport, Conn. : Praeger Security International, 2006)
"The basic argument of this book is that liberal democracy is a security imperative in today's global security environment. Since terrorist groups change and evolve, the best way for states to win legitimacy vis-a-vis these organizations is by adhering to liberal democratic values, cooperating with other states, and applying prudent counterterrorist tactics. As the United States assesses its homeland defense posture, it must resist any temptation to weaken its liberal democratic values, encouraging other states to adhere to liberal democratic values as well."--Jacket.
The Basques in Spain and repercussions in France: case I -- The Kurds in Turkey: case II -- The ethnic Albanians in Macedonia: Case III -- Thfailure of Russian democratization and the tragedy of Chechnya: case IV.
Includes bibliographical references (pages 137-171) and index.
Keywords: Terrorism -- Prevention; Democratization; Legitimacy of governments; Political stability; Separatist movements -- Case studies; National liberation movements -- Case studies; Case studies